2015
DOI: 10.3892/ijmm.2015.2354
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic stretch enhances bone morphogenetic protein-2-induced osteoblastic differentiation through the inhibition of Hey1

Abstract: Substantial evidence has indicated that osteoblastic differentiation may be regulated by mechanical loads or bone morphogenetic protein-2 (BMP-2). BMP-2-induced in vivo osteogenesis can be significantly enhanced in the presence of mechanical stimuli, revealing the therapeutic potential of the combined application of BMP-2 and mechanical loads in clinical bone diseases (e.g., bone fractures and osteoporosis); however, the underlying mechanisms remain elusive. In this study, we found that cyclic stretch or BMP-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 36 publications
1
23
1
Order By: Relevance
“…A vibrational force that is perpendicularly induced at peak acceleration results in increased pro-osteogenic gene expression, even though smaller maximum strains \20 l strain were observed at 60 Hz and at 1.0 or 5.0 m/s 2 , respectively. This is in contrast with prior work describing enhanced osteoblast differentiation with 0.1 Hz of cyclic stretch (Zeng et al 2015). They found that a 10 % elongation (or a 1 9 10 5 l strain) was necessary to upregulate Runx2 gene expression.…”
Section: Discussioncontrasting
confidence: 55%
“…A vibrational force that is perpendicularly induced at peak acceleration results in increased pro-osteogenic gene expression, even though smaller maximum strains \20 l strain were observed at 60 Hz and at 1.0 or 5.0 m/s 2 , respectively. This is in contrast with prior work describing enhanced osteoblast differentiation with 0.1 Hz of cyclic stretch (Zeng et al 2015). They found that a 10 % elongation (or a 1 9 10 5 l strain) was necessary to upregulate Runx2 gene expression.…”
Section: Discussioncontrasting
confidence: 55%
“…In contrast, in MC3T3 cells, cyclic tension resulted in Hey1 expression similar to that at baseline. However, BMP-2-induced Hey1 expression was attenuated (Zeng et al, 2015). Further, it has been shown in vitro that the application of static compressive force on hPDLs resulted in increased JAG1 expression (Kikuta et al, 2015), Moreover, Jagged1 and Notch2 protein expression were increased in PDL tissue on the compressive side of rat teeth subjected to orthodontic force (Kikuta et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Early osteoprogenitors can respond with the expansion of clonal proliferation and the enhancement of differentiation [9,10]. MC3T3-E1, a widely used preosteoblast lineage cell, is further promoted to differentiate and mineralize by mechanical stimuli, as evidenced by the increase in special gene markers [11,12]. In contrast, the absence of mechanical stimulation is able to inhibit the processes of MSC proliferation and osteogenic differentiation [13,14], increases osteoblast sensitivity to apoptosis and regression [15,16], and finally leads to a decreased rate of bone formation.…”
Section: Introductionmentioning
confidence: 99%